(untitled) (Research, Society and Development, 2020)
Historical wind speed series from the databases of the National Institute of Meteorology (INMET) and ECMWF Re-Analyzes (ERA-40) were analyzed in order to quantify the degree of regularity of the time series and the degree of similarity between the databases of conventional stations (INMET) and reanalysis (ERA-40), using the Sample Entropy and cross-Sample Entropy methods of information theory. Due to the lack of information in the INMET database, the analyzes were carried out over a period of eight years of simultaneous data (1993 to 2000) for the INMET and ERA-40 database, during 00h, 12h and in the Complete / Total (original series). The results show that the largest wind speed records for different series are found in the North of the four sub-regions of the NE. Sample Entropy showed greater regularity of wind speed in the Middle North, an area where wind speed is lower, with better predictability in this area. The cross-Sample Entropy showed a moderate synchronization of the INMET and ERA-40 series, indicating an overestimation or underestimation of the ERA-40 data in relation to the INMET data.